Microsoft SQL server 2008 integration services unleashed - Haselden, Kirk (Sams, 2009)
Through clear, concise explanations and samples, you'll grasp a clear understanding of working in the integration services environment, including how to set up stock components, how to use the various designer features, and how to gain practical knowledge on configuring, deploying, securing, and managing packages.